Dehydrative Nazarov-type electrocyclizations of alkenyl (hetero)aryl carbinols via calcium catalysis: Access to cyclopenta[b]thiophenes and indene derivatives. Issue 29 (20th July 2017) - Martin, M. Cynthia; Sandridge, Matthew J.; Williams, Corey W.; Francis, Zola A.; France, Stefan
Abstract: A general approach to the understudied cyclopenta[ b ]thiophenes is reported. The products were directly generated from calcium-catalyzed, dehydrative, Nazarov-type electrocyclizations of alkenyl thienyl carbinols in up to 82% yield. The thienyl carbinols demonstrated good tolerance for aryl and heteroaryl substituents on the alkene. Aryl carbinols were also amenable to the calcium-catalyzed conditions and afforded indene derivatives in good yields. In most cases, the reaction was selective for the thermodynamic alkene isomer; however, substituent effects played a role in determining product outcomes. Mechanistically, the calcium catalyst initiated formation of alkenyl (hetero)aryl carbinyl cations which subsequently underwent a 4π electrocyclization and elimination that is reminiscent of the Nazarov reaction. This transformation is significant for two main reasons: 1) it represents one of the only examples of catalysis for dehydrative, Nazarov-type electrocyclizations in which thiophene was compatible; 2) it allowed for the direct formation of cyclopenta[ b ]thiophenes while circumventing the need for cyclopenta[ b ]thiophenones as precursors. Graphical abstract: